Prevalence of Endoparasites among Liza abu Fishes in a Private Farm in Babylon Province Iraq - Al-Dulaimi, Fadhil H.A.; Al-Hamairy , Ahmed. K. A .; Al-Ajeely, Aussama A. M (International Journal of Psychosocial Rehabilitation, 2020)
A total of 142 fish of Liza abu were examined from one of the private fish farm in the Mashroa Al-Musayyib area, Babylon province which feeds from the Euphrates River water in the Al- Musayyib region from the period of December, 2018 till June 2019.The total percentage rate was 46.5%. The incidence of larval stage of the Trematoda Diplostumum spathaecum which was 36.60% and the larval stage of Cestoda Ligula intestinalis which was 25.35 % and the proportion of Oocysts of Cryptosporidium spp. Which was 23.90% and oocysts of Eimeria sp. was (16.20%) also recorded Cryptosporidium spp. where the first time When examining the intestine contents as a spherical badies bright red ranged diameters from 3-7 microns and also studied the season effect and relationship with percentage of parasitic infections.